Preparation and thermal decomposition of solid state compounds of 4-methoxybenzylidenepyruvate with alkali earth metals, except beryllium and radium - deOliveira, LCS; Rasera, D. E.; Siqueira, O. S.; Matos, JR; Melios, C. B.; Ionashiro, Massao [UNESP] (Elsevier B.V., 1996)
Solid compounds of general formula ML(2) . nH(2)O [where M is Mg, Ca, Sr or Ba; L=4 methoxybenzylidenepyruvate (4-MeO-BP); n = 4, 1 or 0] have been synthetized. Thermogravimetry (TG), derivative thermogravimetry (DTG), differential scanning calorimetry (DSC), x-ray diffraction powder patterns and elemental analysis have been used to characterize the compounds. The thermal stability of these compounds as well as that of the decomposition products were studied using Pt or Al2O3 crucibles in an air or a CO2 atmosphere.
Keywords: 4-methoxybenzylidenepyruvate; alkali earth metals; thermal decomposition